The skillful teacher on technique, trust, and responsiveness in the classroom - Brookfield, Stephen. (Jossey-bass higher and audlt education series, 2006)
Experiencing teaching -- The core assumptions of skillful teaching -- Understanding our classrooms -- What students value in teachers -- Understanding and responding to the emotions of learning -- Lecturing creatively -- Preparing students for discussion -- Getting students to participate in discussion -- Teaching in diverse classrooms -- Giving helpful evaluations -- Teaching online -- Responding to resistance -- Dealing with the politics of teaching -- Surviving emotionally.